STUDENTS’ ATTITUDE ON THE USE OF ARTIFICIAL INTELLIGENCE (AI) IN LEARNING IN THE FACULTY OF EDUCATION, UNIVERSITY OF BENIN, BENIN CITY, NIGERIA - ADEOSUN , PRAISE KEHINDE (Sokoto Educational Review, 2025)
Artificial Intelligence (AI) is a revolutionary technology that’s transforming modern education and institutional structures. As a rapidly evolving field, AI has the potential to significantly alter conventional approaches across various sectors, particularly within academia. Given its growing influence, there is an urgent need for stakeholders to proactively adapt to its integration. This study explores the attitudes of students in the Faculty of Education at the University of Benin towards the use of AI in learning. Employing a survey research design, we used a multistage sampling technique to select a sample of 220 students. Data were collected using a structured instrument titled "Questionnaire on Attitude of Students towards the Use of Artificial Intelligence (QAUAI)," which yielded a reliability coefficient of r=0.717 using Cronbach’s alpha. The instrument was administered to the students by the researcher and two research assistants. We answered the research questions using descriptive statistics such as mean and standard deviation. Findings revealed that students generally exhibited a highly positive attitude toward the application of AI in education. Despite acknowledging its numerous advantages, some students expressed mild reservations about its adoption. Nevertheless, their overall willingness to embrace AI in learning remained strong. Based on these insights, the study recommends that university management implement targeted training programs to enhance AI literacy and provide students with the necessary skills for effective utilization. Furthermore, orientation initiatives should be introduced to deepen students’ understanding of AI’s capabilities. It is also imperative that higher education institutions invest in modern technological infrastructure to alleviate apprehension and foster student confidence in digital learning environments. DOI: https://doie.org/10.10318/SER.2025541920